2022
DOI: 10.1039/d2cp00308b
|View full text |Cite
|
Sign up to set email alerts
|

Sniffing out camphor: the fine balance between hydrogen bonding and London dispersion in the chirality recognition with α-fenchol

Abstract: Binary complexes between the chiral monoterpenoids camphor and α-fenchol were explored with vibrational and rotational jet spectroscopy as well as density functional theory in order to explore how chirality can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
“…This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low-energy isomers of weakly bound complexes. 50,51,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high-confidence determination of the analyte absolute configuration.…”
Section: Discussionmentioning
confidence: 99%